Remote sensing of land cover change dynamics in mountainous catchments and semi-arid environments: a review - Anothando Yono; Retang Anna Mokua; Timothy Dube (Geocarto International)
This paper investigates the impacts and dynamics of land use/land cover (LULC) change dynamics in mountainous catchments in semi-arid regions, focusing on drivers, methods, and hydrological impacts. This study reviews studies using the application of remotely sensed data and spatially modified data, highlighting advancements in LULC assessments through GIS integration and predictive modelling. Key drivers include agricultural expansion, population growth, urbanisation, and infrastructure development, which transform forests and grasslands into built environments, affecting ecosystem services and biodiversity. LULC changes significantly impact hydrology, leading to increased surface runoff, poor water quality, and disruptions in the hydrological cycle. Agricultural expansion also contributes to habitat fragmentation ad biodiversity loss. This study underscores the importance of sustainable land management and informed policy decisions to mitigate negative impacts and enhance ecological resilience in semi-arid regions.